2022
DOI: 10.1002/ece3.8844
|View full text |Cite
|
Sign up to set email alerts
|

Two new hermit crab species ofDiogenes(Crustacea: Decapoda: Diogenidae) from Atlanto‐Mediterranean coasts of Iberian Peninsula: Poleward migrants or merely overlooked indigenous species?

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 60 publications
0
2
0
Order By: Relevance
“…These species have long been considered variations of the highly polymorphic D. pugilator (Forest and Guinot 1956, Ingle 1993, Noël 2016. Recent studies have demonstrated that there are in fact different species, which can be separated on the basis of several morphological characters that are not always easy to recognize and show a certain degree of intraspecific variation (Almón et al 2022a(Almón et al , 2022b. However, despite the possible variations that may occur, general colour patterns are consistently different between the four species for which this information is available.…”
Section: Discussionmentioning
confidence: 99%
“…These species have long been considered variations of the highly polymorphic D. pugilator (Forest and Guinot 1956, Ingle 1993, Noël 2016. Recent studies have demonstrated that there are in fact different species, which can be separated on the basis of several morphological characters that are not always easy to recognize and show a certain degree of intraspecific variation (Almón et al 2022a(Almón et al , 2022b. However, despite the possible variations that may occur, general colour patterns are consistently different between the four species for which this information is available.…”
Section: Discussionmentioning
confidence: 99%
“…Edwardsii group is characterized by the simple intercalary rostral process, non-bifurcate antennal acicles, antennal and antennular peduncles being distinctly longer than the ocular peduncles, and a long and setose antennal flagellum (Asakura and Tachikawa 2010). The group comprises 49 species and are found throughout Indo-Pacific and East Atlantic (Rahayu 2015;Trivedi et al 2016;Igawa and Kato 2017;Landschoff and Rahayu 2018;Almón et al 2021Almón et al , 2022. So far, 10 species of Diogenes from the Edwardsii group have been identified in Indonesian seas.…”
Section: Introductionmentioning
confidence: 99%